2014
DOI: 10.1007/s10641-014-0346-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgically implanted dummy ultrasonic transmitters on growth, survival and transmitter retention of bighead carp Hypophthalmichthys nobilis

Abstract: The effects of surgically implanted dummy ultrasonic transmitters on growth, survival and transmitter retention of bighead carp Hypophthalmichthys nobilis were investigated from October to November 2010. Before the surgery, 162 bighead carps were divided into three groups: 1) control group: handling but no tagging; 2) sham group: surgical procedure without implantation of dummy ultrasonic transmitter; 3) surgery group: surgical implantation of dummy ultrasonic transmitters. Growth, survival, incision healing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Surgery error, however, was a factor in survival when implanting tags into juvenile bighead carp. Though the methods used for surgical implantation in our experiment were similar to the methods used for implanting juvenile salmonids (Wagner, Cooke, Brown, & Deters, 2011) and for adult bighead carp (Luo et al, 2015), the morphology of small bighead carp posed challenges that likely led to surgery errors. Juvenile bighead carp in the size range used for our experiment are laterally compressed and have a thin body wall in the area where the incision was made.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery error, however, was a factor in survival when implanting tags into juvenile bighead carp. Though the methods used for surgical implantation in our experiment were similar to the methods used for implanting juvenile salmonids (Wagner, Cooke, Brown, & Deters, 2011) and for adult bighead carp (Luo et al, 2015), the morphology of small bighead carp posed challenges that likely led to surgery errors. Juvenile bighead carp in the size range used for our experiment are laterally compressed and have a thin body wall in the area where the incision was made.…”
Section: Discussionmentioning
confidence: 99%
“…Bighead carp Hypophthalmichthys nobilis and silver carp Hypophthalmichthys molitrix (together, bigheaded carps) are invasive fishes in North America that have resulted in substantial negative effects on native fish communities and aquatic ecosystems (Kolar et al, ). The range expansion, movement, and behavior of adult bigheaded carps have been studied previously using telemetry (Coulter & Goforth, ; DeGrandchampGarvey & Colombo, ; Peters, Pegg, & Reinhardt, ) and the effects of the surgical implantation have been documented (Luo, Duan, & Wang, ; Luo, Duan, Liu, & Chen, ). However, similar studies with juvenile bigheaded carps have yet to be attempted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al. (2015) showed the growth effects of bighead carp Hypophthalmichthys nobilis (Richardson, 1845) disappeared gradually until 28 days after tagging. Another bluegill study (Knights & Lasee, 1996) also showed the same situation for up to 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…This encapsulation protected the transmitter, preventing tag expulsion through the incision site or transintestinal expulsion. In fact, the rapid encapsulation of the transmitter has been shown to play a role in retention by limiting its mobility and minimizing the risk of organ damage (Thoreau & Baras, 1997;Penne et al, 2007;Luo et al, 2015). Additionally, the effect of encapsulation processes and incision site on wound healing and tag retention should also be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%